Formulation and Characterization of Nanoemulsion Intranasal Adjuvants: Effects of Surfactant Composition on Mucoadhesion and Immunogenicity - Wong, Pamela T; Wang, Su He; Ciotti, Susan; Makidon, Paul E; Smith, Douglas M; Fan, Yongyi; Schuler, Charles F; Baker, James R (Molecular pharmaceutics, 2014)
The development of effective intranasal vaccines is of great interest due to their potential to induce both mucosal and systemic immunity. Here we produced oil-in-water nanoemulsion (NE) formulations containing various cationic and nonionic surfactants for use as adjuvants for the intranasal delivery of vaccine antigens. NE induced immunogenicity and antigen delivery are believed to be facilitated through initial contact interactions between the NE droplet and mucosal surfaces which promote prolonged residence of the vaccine at the site of application, and thus cellular uptake. However, the details of this mechanism have yet to be fully characterized experimentally. We have studied the physicochemical properties of the NE droplet surfactant components and demonstrate that properties such as charge and polar headgroup geometry influence the association of the adjuvant with the mucus protein, mucin. Association of NE droplets with mucin in vitro was characterized by various biophysical and imaging methods including dynamic light scattering (DLS), zeta potential (ZP), and surface plasmon resonance (SPR) measurements as well as transmission electron microscopy (TEM). Emulsion surfactant compositions were varied in a systematic manner to evaluate the effects of hydrophobicity and polar group charge/size on the NE–mucin interaction. Several cationic NE formulations were found to facilitate cellular uptake of the model antigen, ovalbumin (OVA), in a nasal epithelial cell line. Furthermore, fluorescent images of tissue sections from mice intranasally immunized with the same NEs containing green fluorescent protein (GFP) antigen demonstrated that these NEs also enhanced mucosal layer penetration and cellular uptake of antigen in vivo. NE–mucin interactions observed through biophysical measurements corresponded with the ability of the NE to enhance cellular uptake. Formulations that enhanced antigen uptake in vitro and in vivo also led to the induction of a more consistent antigen specific immune response in mice immunized with NEs containing OVA, linking NE-facilitated mucosal layer penetration and cellular uptake to enhancement of the immune response. These findings suggest that biophysical measurement of the mucoadhesive properties of emulsion based vaccines constitutes an effective in vitro strategy for selecting NE candidates for further evaluation in vivo as mucosal adjuvants.